2007
DOI: 10.1111/j.1745-7599.2007.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of autonomy of nurse practitioners in an acute care setting

Abstract: The results of this study provided preliminary evidence of the level of autonomy of NPs providing inpatient care to adult patients in an acute care setting. The findings could lead to future research on the impact of NP services on patient outcomes and clinical productivity in acute care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
67
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 36 publications
14
67
2
1
Order By: Relevance
“…12,14,15 On a daily basis, in an effort to reduce hospital length of stay, mortality and morbidity, and hospital readmission rates, the ACNP is constantly evaluating avenues to contain cost while providing safe and efficient care, increase patient satisfaction, and ensure the plan of care comprises action plans to ensure patient safety. 8,10,12,16,17 As a result of the ACNP's consistent vigilance over these clinical indicators, patients who received care from ACNPs had the same clinical outcomes as patients who were managed by hospitalist-led care. 14,17 This case study highlights the role of an ACNP caring for an acutely ill patient hospitalized over 70 days.…”
Section: Review Of the Literaturementioning
confidence: 90%
See 2 more Smart Citations
“…12,14,15 On a daily basis, in an effort to reduce hospital length of stay, mortality and morbidity, and hospital readmission rates, the ACNP is constantly evaluating avenues to contain cost while providing safe and efficient care, increase patient satisfaction, and ensure the plan of care comprises action plans to ensure patient safety. 8,10,12,16,17 As a result of the ACNP's consistent vigilance over these clinical indicators, patients who received care from ACNPs had the same clinical outcomes as patients who were managed by hospitalist-led care. 14,17 This case study highlights the role of an ACNP caring for an acutely ill patient hospitalized over 70 days.…”
Section: Review Of the Literaturementioning
confidence: 90%
“…ACNPs in acute care settings reported increased satisfaction in their role because of their autonomy and collaborative care and were highly skillful and competent while managing patients requiring high-level, comprehensive care. 8,9 First and foremost, ACNPs are patient advocates. The ultimate goal of the ACNP is to provide the best evidence-based care possible and ACNPs have been proven to be successful in numerous departments.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Cajulis & Fitzpatrick (2007) designed a descriptive study to determine the level of autonomy of NPs in an acute care setting, trained as adult nurse practitioners (ANPs), ACNPs, geriatric nurse practitioners (GNPs), and family nurse practitioners (FNPs). The study was conducted in a large metropolitan hospital and the sample population was NPs practicing with adults inpatients (n = 54).…”
Section: Advanced Practice Nurse (Apn) Intensivist Servicesmentioning
confidence: 99%
“…Around 50% of NPs had very high levels, 31.5% had extremely high levels, and 19% had moderate levels of autonomy. Data revealed that the majority of the NPs were highly empowered, accountable, and responsible in providing care in acute care settings (Cajulis & Fitzpatrick, 2007). The heavy demand for critical care services in the U.S. is growing; almost 55,000…”
Section: Advanced Practice Nurse (Apn) Intensivist Servicesmentioning
confidence: 99%